2000
DOI: 10.1007/s002849910041
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Bacillus thuringiensis on Cured Tobacco Leaves

Abstract: A worldwide survey was conducted to evaluate the frequency and distribution of Bacillus thuringiensis populations on cured tobacco leaves during post-harvest storage. In total, 133 tobacco samples of different types and origins were analyzed. Nine percent of the samples showed the presence of B. thuringiensis, and 24 B. thuringiensis strains were isolated and characterized. The majority of the isolates produced bipyramidal crystals, and three fourths of them showed a second type of crystal protein (cuboidal or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…English et al () revealed that B. subtilis and B. circulans could hasten the development of desirable flavors and improve the smoking qualities of cigar tobacco. B. thuringiensis, which produces bipyramidal crystals, is present on the tobacco leaf surface and can control insect pests that affect stored tobacco (Kaelin & Gadani, ). B. subtilis has a strong ability to control the effects of tobacco black shank (Han et al, ) and displayed an antagonistic effect against Verticillium dahliae , which causes verticillium wilt (Berg & Ballin, ).…”
Section: Discussionmentioning
confidence: 99%
“…English et al () revealed that B. subtilis and B. circulans could hasten the development of desirable flavors and improve the smoking qualities of cigar tobacco. B. thuringiensis, which produces bipyramidal crystals, is present on the tobacco leaf surface and can control insect pests that affect stored tobacco (Kaelin & Gadani, ). B. subtilis has a strong ability to control the effects of tobacco black shank (Han et al, ) and displayed an antagonistic effect against Verticillium dahliae , which causes verticillium wilt (Berg & Ballin, ).…”
Section: Discussionmentioning
confidence: 99%
“…Bacillus spp. have also been identified in cured tobacco leaves (Kaelin and Gadani 2000), stored tobacco (Kaelin et al 1994), dead tobacco beetles (Kaelin et al 1994), and chewing tobacco sold in the United States (Rubinstein and Pedersen 2002). …”
Section: Discussionmentioning
confidence: 99%
“…The naturally occurring crystals in B. thuringiensis IS5056 were observed to be very large The shape of the IS5056 CryAb21 inclusion is atypical for Cry1-type protein crystals (2,14,27), and this enabled us to use it as a marker for our experiments in which we examined the reproduction of B. thuringiensis in T. ni. With respect to the atypical shape of the IS5056 crystal, it is known that the native shapes of Cry proteins are largely maintained by interchain disulfide bridges, which can be distorted by physical and chemical treatment (6).…”
Section: Discussionmentioning
confidence: 99%